2016
DOI: 10.3847/0004-637x/832/2/140
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Rapidly Moving Partial X-Ray Absorbers Within Gamma Cassiopeiae

Abstract: Gamma Cassiopeiae is an enigmatic Be star with unusually strong hard X-ray emission. The Suzaku observatory detected six rapid X-ray spectral hardening events called "softness dips" in a ∼100 ksec duration observation in 2011. All the softness dip events show symmetric softness ratio variations, and some of them have flat bottoms apparently due to saturation. The softness dip spectra are best described by either ∼40% or ∼70% partial covering absorption to kT ∼12 keV plasma emission by matter with a neutral hyd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 46 publications
1
30
0
1
Order By: Relevance
“…In the X-rays, however, γ Cas is quite anomalous. Previous observations (Mason et al 1976;Frontera et al 1987;White et al 1982;Murakami et al 1986;Horaguchi et al 1994;Haberl 1995;Smith et al 1998;Kubo et al 1998;Owens et al 1999;Robinson & Smith 2000;Robinson et al 2002;Smith et al 2004b;den Hartog et al 2006;Lopes de Oliveira et al 2010;Shrader et al 2015;Hamaguchi et al 2016) revealed an X-ray luminosity of ∼10 32−33 erg s −1 , the lack of drastic flux variations such as X-ray outbursts, the presence of the Fe K complex resolved into three emission lines from highly ionized Fe (Fe XXV Heα and Fe XXVI Lyα respectively at 6.7 and 7.0 keV) as well as quasi-neutral Fe (Fe I Kα at 6.4 keV). It has an exceptionally high plasma temperature beyond ∼10 keV, which is unseen in other classes of early-type stars.…”
Section: Introductionmentioning
confidence: 93%
“…In the X-rays, however, γ Cas is quite anomalous. Previous observations (Mason et al 1976;Frontera et al 1987;White et al 1982;Murakami et al 1986;Horaguchi et al 1994;Haberl 1995;Smith et al 1998;Kubo et al 1998;Owens et al 1999;Robinson & Smith 2000;Robinson et al 2002;Smith et al 2004b;den Hartog et al 2006;Lopes de Oliveira et al 2010;Shrader et al 2015;Hamaguchi et al 2016) revealed an X-ray luminosity of ∼10 32−33 erg s −1 , the lack of drastic flux variations such as X-ray outbursts, the presence of the Fe K complex resolved into three emission lines from highly ionized Fe (Fe XXV Heα and Fe XXVI Lyα respectively at 6.7 and 7.0 keV) as well as quasi-neutral Fe (Fe I Kα at 6.4 keV). It has an exceptionally high plasma temperature beyond ∼10 keV, which is unseen in other classes of early-type stars.…”
Section: Introductionmentioning
confidence: 93%
“…2), the periodogram appears similar to that found for HD 110432 with Chandra (Torrejón et al 2012); it does not show a clear 1/ f trend, as detected notably in γ Cas by Lopes de Oliveira et al (2010), probably because of the larger noise in our data. This noise also prevents us from significantly detecting very short events associated with increased absorption (Hamaguchi et al 2016).…”
Section: Temporal Variabilitymentioning
confidence: 99%
“…The origin of this peculiar X-ray emission is still under debate, with two main scenarios under consideration: accretion onto a compact object (a white dwarf, see e.g. Hamaguchi et al 2016;Tsujimoto et al 2018, or a neutron star in a propeller regime, see e.g. Postnov et al 2017), or star-disk interactions (Smith et al 2016, and references ⋆ Based on spectra obtained with Aurélie at OHP and with FEROS and UVES at ESO, as well as on data collected with the SMEI, BRITE, and TESS space missions.…”
Section: Introductionmentioning
confidence: 99%